A provenance study on the ceramics excavated at the Varzaneh Plain, central Iran - Parviz Holakooei; Babak Rafiei-Alavi; Ali Shojaee-Esfahani; Yaser Jebreili; Sepehr Bahadori; Rebecca Piovesan; Lara Maritan (Heritage Science)
Abstract Forty-six ceramic shards from the Early Bronze Age (EBA) archaeological site of Tappeh Gabri (the archaeological site 013), dated back to the latter half of the third millennium BCE and located at the Varzaneh Plain, central Iran, were studied using micro energy dispersive X-ray fluorescence (µ-EDXRF) and petrographic analysis. The precision and accuracy of quantitative data obtained by µ-EDXRF were tested using a series of geological certified reference materials (CRM). The expanded uncertainty and the Mantel test on data obtained by µ-EDXRF showed accurate and precise quantitative µ-EDXRF estimation of elements present in the CRMs above their quantification limit. We show that the majority of the ceramics at the Varzaneh Plain is most probably local product. Discussions prompted collecting further compositional data and performing petrographic investigation from the ceramic shards from southern and south-western Iran in order to shed light on the origin of the ceramic shards excavated at the Varzaneh Plain.